Analysing labels, associations, and sentiments in Twitter on the Abu Sayyaf kidnapping of Viktor Okonek - Reyes, Joseph Anthony L. (Terrorism and political violence, 2017)
This article investigates Twitter data related to the kidnapping case of two German nationals in the southern region of the Philippines by the Abu Sayyaf Group (ASG). It explores perceptions of the ASG, along with associated organizations and sentiments indicated in the tweets together with statistically significant relationships. Findings revealed that: “Rebel” and “Militant” were the most frequently used labels for the ASG; a majority of the tweets contained sentiments that assess threats such as abduction and kidnapping of hostages; and almost half contained words that indicate negotiation or concession to the demands of the captors. Logistic regression analyses on “Rebel” and “Islamist” revealed positive coefficients for these sentiments used as predictors. This meant that people who assessed threats and expressed sentiments that responders should concede to the captors’ demands were more likely to use the “Rebel” or “Islamist” labels. Rather than the two longstanding dominant narratives of the ASG as terrorists and criminals, the emerging rebel and militant labels suggest a more domestically and politically sensitive Twitter commentary than is represented in the work of the Al-Qaeda-centric paradigm exponents. These findings, along with the complex associated political and policy contexts and implications, are discussed in this article.